Recent Advances in Heterostructured Carbon Materials as Anodes for Sodium‐Ion Batteries. Issue 12 (31st October 2021) - Zhao, Rui; Sun, Ning; Xu, Bin
Abstract : Carbon materials have attracted extensive attention as anodes for sodium‐ion batteries (SIBs) because of the abundant resources, low cost, and diverse structure. Due to the different structure configurations, hard carbons, soft carbons, as well as nanocarbons present distinct electrochemical Na‐storage behaviors and properties. The diverse structural and chemical characteristics of carbon materials' precursors have paved pathways to construct a robust carbon‐based heterostructure with enhanced electrochemical performances. This review comprehensively discusses the fabrication of carbon‐based heterostructures, including hard–hard, hard–soft, and hard–nano heterostructures, with a focus on the formation processes and the benefits of these heterostructures in Na‐ion storage. Furthermore, the key obstacles and potential production of such heterostructures are explored, disclosing future structural design of high‐performance carbon‐based anode materials for SIBs. Abstract : This review summarizes the recent progress in the fabrication of carbon‐based heterostructures, with a focus on the formation processes and the benefits of these heterostructures in Na‐ion storage.